Patent prospecting of biosorbents used for oil and derivatives sorption (Research, Society and Development, 2022)
Oil and derivatives leaks are growing concerns worldwide, as they harm the environment, the socio-economic sector, and human beings. Therefore, alternative, and sustainable ways, such as bioadsorption with vegetable fibers, have been studied to clean these oils and derivatives effectively and non-aggressively. In this work, a patent prospection was carried out in the Espacenet® database and the National Institute of Industrial Property - (INPI). The evolution, origin, and applications were analyzed, and the most used fibers in the patents were found. As a result, the first patent was filed in 1999, and the countries that filed the most patents were Japan (45%), Brazil (28%), and China (25%). It is also seen that the most used fibers are cotton and coconut due to their wide availability around the world. Therefore, the development of technologies that use vegetable fibers to clean spilled oil and derivatives has excellent potential since they are environmentally and economically favorable.